Penerapan model pembelajaran problem based learning berbantuan media komik untuk meningkatkan keterampilan pemecahan masalah siswa kelas v sekolah dasar - Riska Sulistyowati; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Universitas Sebelas Maret, 2024)
This study aimed to: 1) describe the implementation of Problem-Based Learning (PBL) with comic media to enhance problem-solving skills in fraction story problems; 2) improve problem-solving skills in fraction story problems through the PBL instructional model. This research used a Classroom Action Research methodods. The subjects were teachers and 34 fifth-grade students. Data collection techniques are observation, interviews, documentation, and tests. Data validity was using triangulation. The data analysis technique was interactive analysis. The result showed that the average problem-solving skill score increased in each cycle. In the pre-action phase, it was 66,76, in cycle 1 it was 75,15, and it became 87,74 in cycle 2. Classical completeness also increased, from 41% in the pre-action phase to 53% in cycle 1, and 88% in cycle 2. The study concluded that: 1) the PBL model assisted by comic media was effectively imlemented; 2) the problem-solving skills of fifth-grade students at SD Negeri Jajar Surakarta improved using the model and media. Theoretical implications provided information using PBL models with comic media in teaching mathematical. Practical implications showed that applying PBL with comic media was effective and had a positive impact.This study can be a reference for other researchers.